Copy number control of a transposable element, the I factor, a LINE-like element in Drosophila. - Chaboissier, M.C.; Bucheton, A.; Finnegan, D.J. (Proceedings of the National Academy of Sciences of the United States of America, 1998)
The I factor is a LINE-like transposable element in Drosophila. Most strains of Drosophila melanogaster, inducer strains, contain 10-15 copies of the I factor per haploid genome located in the euchromatic regions of the chromosome arms. These are not present in a few strains known as reactive strains. I factors transpose at low frequency in inducer strains but at high frequency in the female progeny of crosses between reactive and inducer flies. We have found that the activity of the I factor promoter is sensitive to the number of copies of the first 186 nucleotides of the I factor sequence, which constitutes the 5'-untranslated region. The activity of the I factor decreases as the copy number of this sequence increases.